Approximate Triangulations of Grassmann Manifolds - Kevin P. Knudson (Algorithms, 2020)
We define the notion of an approximate triangulation for a manifold M embedded in Euclidean space. The basic idea is to build a nested family of simplicial complexes whose vertices lie in M and use persistent homology to find a complex in the family whose homology agrees with that of M. Our key examples are various Grassmann manifolds <semantics> G k ( R n ) </semantics> .